PUGAI (FUMIGATION) AS A PURA MARUTHUVAM (EXTERNAL THERAPY) IN THE SIDDHA SYSTEM OF MEDICINE - Lalitha, *S.; Anavarathan, V.; Mahalakshmi, V.; Kumar, N. J. Muththu kumar (International Journal of Ayurveda and Pharma Research, 2018)
Siddha Medicine is a traditional system of healing medicine in the southern part of the India and some other nations. This system of Medicine is mainly categorized into two classes, based on the root of admiration of the drugs, which are 32 types of Aga marunthugal (Internal medicine) and 32 types of Pura marunthugal (External medicine) for treating the 4448 diseases describe in the Siddha texts. The 32 types of External therapies are included in many kinds of external application of treatment procedures. Siddha texts mentioned the Pugai is termed as Fumigation is one of the external therapies in this system. This study reveals that the Pugai is the effective external treatment procedure to cure some disease condition based on Siddha theory. Fumigation signifies the artificial impregnation of the atmosphere, with the fumes or smoke of any vegetable or aromatic substances. Pugai is an application of fumes is administered in different parts of the body, apart from inhalation. Most of these therapies are aimed to maintaining the healthy balance of tri humours of Vatham, Pitham, Kabam and Saptha thathukkal which mean seven tissue types of the body. Main purpose of this procedure is to reduce microbes and to control infections. Fumigation can be effective in inactivating microbes on environmental surfaces.